Combined effect of phosphate fertilizer types and dripline depth on distribution of nitrogen and phosphorus in soil and maize yield - WANG Huiyun; WANG Zhen; RAN Yanli; LI Xiumei (Guan'gai paishui xuebao)
【Objective】 Subsurface drip fertigation is an irrigation technique to simultaneously deliver water and dissolved nutrients into the root zone. Its efficacy depends on many factors. In this paper, we investigate the combined effect of phosphate fertilizer types and dripline depth on distribution of nitrogen and phosphorus in soil and grain yield of maize. 【Method】 The experiments were conducted in tanks grown with maize in a rain shelter, using two types of fertilizers: ammonium polyphosphate (APP, P1) and monoammonium phosphate (MAP, P2). The control is no fertilization (CK). The driplines were buried at the depths of 0 cm (D1) and 15 cm (D2). In each treatment, we measured the spatial variation of nitrogen and phosphate, as well as grain yield. 【Result】 Nitrogen applied in the drip fertigation can move to the edge of the maize roots and accumulate there, while the phosphorus was absorbed by soil. The polymerized phosphate fertilizer (P1) weakened soil adsorption and fixation compared to the normal phosphate fertilizer (P2). Soil available phosphorus content in the APP was 15% higher than that in MAP. Irrigation facilitated phosphorus movement in soil and improved uniformity of its distribution, with the bioavailable phosphorus in D2 being 17% higher than in D1. Phosphorus application significantly promoted root growth, with the root length density at the jointing stage being 35% and 19% higher in P1 and P2 than in CK, respectively. It was also found that D2 increased root length density by 12%, compared to D1. Phosphorus application increased bioavailable phosphorus and root length density. This in turn enhanced dry matter accumulation and root uptake of nitrogen and phosphorus, thereby increasing the final grain yield. P1 increased the grain yield by 3% compared to P2, and 21% compared to CK. 【Conclusion】 Our results showed that subsurface fertigation using APP reduced soil phosphorus adsorption, which in turn promoted maize growth and increased the final grain yield.